Internalisasi Nilai Islam Moderat di SMPS Muhammadiyah Plus Bengkalis - Fikri, Muhammad; Zulfila, Zulfila (MAN 4 Kota Pekanbaru, 2022)
Several kinds of research conducted by several institutions show the high value of intolerance in Indonesia, especially among students. Muhammadiyah, one of the largest, oldest organizations and the formulator of the establishment of the Unitary State of the Republic of Indonesia, has a strategic role in preventing radicalism and intolerance. This study aims to determine the internalization of moderate Islamic values at SMPS Muhammadiyah Plus Bengkalis. This research is qualitative. Data collection by Interview, Observation, and Documentation. The data analysis technique in this study will use the Interactive Model technique, which consists of Data Collection, Data Reduction, Data Presentation, and Conclusion Drawing. The results of this study indicate that the Internalization of Moderate Islamic Values at SMPS Muhammadiyah Plus Bengkalis consists of three stages: Value Transformation, Value Transactions, and Trans-Internalization of Values. In contrast, the internalized values are Tasamuh (tolerance), I'tidal (straight and firm), Tawazun (balance), Musawah (equality), and Shura (deliberation).